SUPPORT MANAGEMENT OF PROFESSIONAL AND EDUCATIONAL TRAJECTORY OF STUDENTS UNDER THE CONDITIONS OF SOCIAL AND CULTURAL EDUCATIONAL ENVIRONMENT OF THE UNIVERSITY - Vladimirovna Yakovleva, Elena; Pryazhnikova, Elena; Alekseevich Pugachev, Ivan; Vladimirovna Akhmetshina, Iuliana; Stanislavovna Andryushchenko, Irina; Liudmila Pavlovna, Yarkina; Ivanovna Chernyshova, Lidiya (Revista Inclusiones, 2019)
Recent dramatic transformations have led to the necessity of change Russian educational system, to reinterpretation of the idea of education in our country. It is necessary to pay more and more attention to the preparation of the university students for work in the rapidly changing conditions of social and professional activity. The transformations carried out in the political and socio-economic life of the society, affirm a new look at the personality of a graduate, require professionally trained, self-thinking people, which, in its turn, led to the transition to the new personality-oriented educational standards of the third generation. Federal state educational standards of higher professional education (hereinafter referred to as the FSES of HPE), which meet the need of the modern transition to personality-oriented educational standards, open up new opportunities for students and teachers, which take into account the individual characteristics and personal qualities of students, and ascertain the possibilities for preparing students as subjects of their own vocational education.